The Effect of Current Ratio and Debt To Asset Ratio on Return On Asset Pt Electronic City Indonesia Tbk (ECII) Period 2012 - 2022 - syaihu herais, ahmad (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2024)
This research aims to test and analyze the influence of the Current Ratio and Debt to Asset Ratio on Return on Assets, this research was conducted at PT. Elektronic City Indonesia Tbk Period 2012 – 2022. The results of this research show that, Current Ratio (CR) does not have a significant influence on Return on Assets (ROA), the calculated T value < T Table (2,248 < 2,306) is reinforced with sig > 0, 05 (0.074 > 0.05) Debt to Asset Ratio has a significant influence obtained by the value Tcount > Ttable (3.543 > 2.306) with a strengthened Sig < 0.05 (0.003 < 0.05) and based on the f test between CR and DAR The above ROA shows a simultaneous influence, it can be seen that the results of the calculated F test > F table (6,033 > 4,459), this is reinforced by the Sig value < 0.05 (0.022 < 0.05).